Growth, productivity and rhizospheric behaviour of wheat (Triticum aestivum) varieties under delayed planting and zinc application - KUMAR, AMIT; DHAR, SHIVA; DASS, ANCHAL; RANJANA, RANJANA (The Indian Journal of Agricultural Sciences, 2020)
Field investigation was conducted during rabi seasons of 2013-14 and 2014-15 at the Indian Agricultural Research Institute, New Delhi to study growth, productivity and rhizospheric response of wheat [Triticum aestivum (L.) emend. Fiori & Paol.] varieties under different sowing times and Zn applications. The experiment was laid out in split-plot design, replicated thrice.Treatment consisted of sowing times (normal and very late) and wheat varieties (HD 2967, WR 544 and HD 3059) in main-plots and ZnSO4.7H2O application (control, 25 kg ha−1 soil application, three foliar sprays @ 0.5% at boot, anthesis and grain filling stage, 25 kg ha−1 soil application + one foliar spray @ 0.5% at anthesis) in sub-plots. Wheat growth parameters and grain yield were reduced under very late sowing. Among varieties, WR 544 exhibited higher growth rate, highest grain yield reduction was found with HD 2967.Root growth (RLD, RSA, RV and RWD) lowered at 0−15 cm and improved at 15-30 cm soil depth owing to delayed planting. Higher root growth at 15-30 cm soil depth was noticed with delayed planted HD 3059 which also manifested least yield reduction. Soil application of ZnSO4.7H2O @ 25 kg ha−1 + one foliar spray of 0.5% ZnSO4.7H2O at anthesis recorded higher productivity and root growth of wheat nonetheless was found statistically on par with other Zn levels.